The cry of the hangman - Calkins, Susanna (Calkins, Susanna. Lucy Campion mysteries., 2021)
Murder always sells. But when a series of dark and puzzling crimes takes place in seventeenth-century London, will printer's apprentice Lucy Campion be publishing the news - or starring in it? London, 1667. Printer's apprentice Lucy Campion is unsettled when, on a frozen December morning after church, an elderly woman dressed in mourning clothes whispers an ominous warning in her ear. Lucy sternly tells herself it's nonsense, but then her much-loved former master, Magistrate Hargrave, is viciously attacked with a brass hourglass during a break-in. But what exactly was the intruder searching for? And why did they first stop to steal a piece of Cook's lamb and lentil pie? The puzzling case is just the start of a series of dark, bizarre crimes. Lucy's determined to uncover the truth and see that justice is done. But someone is equally determined to stop her - whatever it takes. This page-turning historical mystery set in Renaissance London is a great choice for readers who like their heroines lively, their mysteries twisty and their historical settings brimming with authenticity.